RANCANG BANGUN SISTEM INFORMASI PERUSAHAAN PT LEON TEKNOLOGI GLOBAL - whisky; Amrizal (LPPM Universitas Putera Batam, 2022)
The website is one of the technological advances, especially regarding the pages on the internet that are frequently visited. Since the internet works as a bond between sender and recipient, there are several things that can be used with it. Many companies are already using information systems to simplify the data processing process because it can make the existing processes in the company more improved. Therefore, it is necessary to design a company system for PT Leon Teknologi Global on a website basis. The approach that will be employed in this study is the waterfall method or SDLC. can more easily place orders and unite users of their orders thanks to the construction of a web-based company information system.